Evaluating the efficacy of restoration plantings through DNA barcoding of frugivorous bird diets. Issue 4 (19th April 2016) - Galimberti, A.; Spinelli, S.; Bruno, A.; Mezzasalma, V.; De Mattia, F.; Cortis, P.; Labra, M.
Abstract: Frugivores are critical components of restoration programs because they are seed dispersers. Thus, knowledge about bird–plant trophic relationships is essential in the evaluation of the efficacy of restoration processes. Traditionally, the diet of frugivores is characterized by microscopically identifying plant residues in droppings, which is time‐consuming, requires botanical knowledge, and cannot be used for fragments lacking detectable morphological characteristics (e.g., fragmented seeds and skins). We examined whether DNA barcoding can be used as a universal tool to rapidly characterize the diet of a frugivorous bird, Eurasian blackcap (Sylvia atricapilla). We used the DNA barcoding results to assess restoration efforts and monitor the diversity of potentially dispersed plants in a protected area in northern Italy. We collected 642 Eurasian Blackcap droppings at the restored site during the autumn migration over 3 years. Intact seeds and fragmented plant material were analyzed at 2 plastidial barcode loci ( rbcL and trnH‐psbA ), and the resulting plant identifications were validated by comparison with a reference molecular data set of local flora. At least 17 plant species, including 7 of the 11 newly transplanted taxa, were found. Our results demonstrate the potential for DNA barcoding to be used to monitor the effectiveness of restoration plantings and to obtain information about fruit consumption and dispersal of invasive or unexpected plant species. Such an approach provides valuable information that could be used to study local plant biodiversity and to survey its evolution over time.